DEVELOPMENT OF INFORMATION SYSTEM FOR BOARDING HOUSES - Betty Dewi Puspasari; Joseph Dedy Irawan; Ridho Arif Wicaksono; Dimas Rizky Pratama; Ahmad Bahrul Ilmi (Computer Science Department, Malang National Institute of Technology, 2025)
The management of boarding houses through manual bookkeeping still faces many challenges, such as recording errors, difficulty in monitoring room availability, and inefficiencies in communication between the manager and tenants. boarding houses face these issues, which can potentially lead to conflicts due to misinformation regarding billing and room status.To address these problems, this study aims to develop a web-based boarding house management information system integrated with WhatsApp as a billing notification tool. This system is designed to reduce recording errors, improve room management efficiency, and facilitate communication between tenants and the boarding house manager.With the implementation of this system, it is expected that boarding house managers can easily access tenant data, monitor room status in real-time, and automate the billing process for tenants. The expected outcome of this system development is improved efficiency in boarding house management, increased data recording accuracy, and ease of monitoring and communication